2012
DOI: 10.1111/j.1365-2028.2011.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation analysis, phenological patterns and chorological affinities in Wadi Qena, Eastern Desert, Egypt

Abstract: The present study, which was conducted between 2009 and 2010, provides an analysis of the floristic composition, life forms, phenology, chorological spectrum and analysis of the vegetation in the deltaic part of Wadi Qena using multivariate analysis techniques. Twenty-five stands were sampled to represent, as much as possible, the vegetation variation in the study area. A total of 54 species (nineteen annuals and 35 perennials) belonging to 47 genera and nineteen families were recorded. The largest families we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
14
14
0
Order By: Relevance
“…Thus the studied species are frequently adapted against drought conditions prevailing in their habitats during summer season, by accumulation of considerable amounts of soluble sugars, soluble proteins and amino acids than in winter when the prevailing ecological conditions may be fairly more favorable for such plants. These results agreed with what was found by Salama et al (2012) on Ochradenus baccatus in Wadi Qena.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus the studied species are frequently adapted against drought conditions prevailing in their habitats during summer season, by accumulation of considerable amounts of soluble sugars, soluble proteins and amino acids than in winter when the prevailing ecological conditions may be fairly more favorable for such plants. These results agreed with what was found by Salama et al (2012) on Ochradenus baccatus in Wadi Qena.…”
Section: Discussionsupporting
confidence: 93%
“…Wadi Qena (220km long) is one of the most notable unique features of the Egyptian Eastern Desert. It runs from north to south (the opposite direction to the Nile Valley) and debouches at the city of Qena 600 km south-East of Cairo (Salama et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of evaporation concentrated the soil solution. The present data agreed with results obtained by Salama et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…The studied species are frequently adapted for drought conditions prevailing in their habitats during the summer season by accumulating more considerable soluble sugars, soluble proteins, and amino acids than in winter when the prevailing ecological conditions may be more favorable for such plants. These results agreed with the study by Salama et al (2012) in Ochradenus baccatus in Wadi Qena.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies revealed the economic potentialities of many species growing naturally within Abu Tartur area such as Abad et al (2007), Kumar and Arya (2006), Atta et al (2005) and Scartezzini and Speroni (2000). Salama et al (2014Salama et al ( , 2012 and Abdel-Aleem (2013) reported that environmental stresses reduce species diversity. Stress due to the hostile climatic aridity is reflected remarkably on the composition and structure of the plant communities.…”
Section: Introductionmentioning
confidence: 99%